Effect of different binder phases on the Σ2 grain boundary plane distribution in cemented carbides - Xiaokun Yuan (Сверхтвердые материалы, 2019)
For WC–6 wt % Co and WC–6 wt % Ni composites, and by using five parameter analysis method as a new approach, the geometric and crystallographic features of carbide/carbide boundaries have been characterized. Two most frequently occurring WC/WC boundaries are 90° twist boundaries about [10-10] (Σ2 boundaries) and 27.8° twist boundaries about [0001] (Σ13a boundaries), the Σ2 boundary populations vary with binder phase types, and carbide crystals are most frequently terminated by (0001) and (10-10) surfaces, such preference does not significantly alter if Σ2 boundaries are partitioned. Визначено геометричні і кристалографічні особливості на межі карбідно-карбідних переходів для композитів WC–6 % (за масою) Co і WC–6 % (за масою) методом аналізу п’яти параметрів. Дві межі WC/WC, що найчастіше зустрічаються, – це поворот межі на 90° приблизно [10-10] (межі Σ2) і поворот межі на 27,8° приблизно [0001] (межі Σ13a), сукупності межі Σ2 змінюються в залежності від типів сполучених фаз і кристалів карбіду і найчастіше закінчуються поверхнями (0001) і (10-10), така перевага суттєво не змінюється, якщо межі Σ2 розділені. Определены геометрические и кристаллографические особенности на границах карбидно-карбидных переходов для композитов WC–6% (по массе) Co и WC–6% (по массе) методом анализа пяти параметров. Наиболее часто встречающиеся две границы WC/WC – это поворот границ на 90°, приблизительно [10-10] (границы Σ2), и поворот границ на 27,8°, приблизительно [0001] (границы Σ13a), совокупности границ Σ2 меняются в зависимости от типов соединенных фаз и кристаллов карбида и чаще всего заканчиваются поверхностями (0001) и (10-10), такое предпочтение существенно не меняется, если границы Σ2 разделены.